Regard écologique sur le recul stratégique : atouts et risques pour la diversité végétale péri-urbaine marseillaise - Laurence Affre; Pierre-Jean Dumas; Estelle Dumas; Isabelle Laffont-Schwob; Thierry Tatoni (VertigO)
The concepts of plant diversity vulnerability are re-contextualized relative to global changes. The scope of the study is on an exceptional area, the rocky peri-urban coastline of Marseille (included in the Calanques National Park) where remarkable and threatened plant communities, named littoral phryganas, can be found. Human habitat destruction and/or degradation generated restricted and fragmented distribution of their populations associated with a high local demographic regression (near absence of recruitment, low reproductive success, high individual necrosis generated by salted / polluted sprays and important inter- specific competition by co-occurrent plants). Face to historical and actual phryganas vulnerability, questions on the impact of a potential rise of sea level and a deconstructed rocky coastline are addressed in an ecological perspective, rarely heard in debates concerning the set-back line strategy. The answers suggest in situ and ex situ management measures but also emerge new questions about the relationship of reciprocity between "urban" and "natural" systems based on a new notion of "living together" in order to effective land management. This is a reminder that it is crucial to combine ecological, social and economic factors in shaping a societal dialogue around issues of biodiversity and implementing concrete actions to habitat conservation.